Cal Tjader The Life and Recordings of the Man Who Revolutionized Latin Jazz - Duncan Reid, S. (McFarland & Company, Inc., Publishers, 2020)
""Within one of the most complex musical categories yet to surface, Cal Tjader quietly pioneered the genre as a jazz vibraphonist, composer, arranger and bandleader from the 1950s through the 1980s. Reid tells the life story of a humble musician, written in a familiar, conversational tone that reveals Tjader's complex charisma. Tjader left behind a legacy and a labyrinth of influence, attested by his large audience and innovation that would change the course of jazz. Expanded and revised, this intimate biography now includes additional interviews and anecdotes from Tjader's family, bandmates, and community, print research, and rare photographs, presenting a full history of an undervalued musician, as well as a detailed account of the progression of Latin Jazz."-Provided by publisher"--